WITH THE USE OF A LIGHT CONCENTRATOR IN SEMICONDUCTOR SOLAR PANEL MODULES AND A BIONIC SUN-TRACKING SYSTEM - Мелентьєв, О.Б. (SWorldJournal, 2025)
This article examines the issue of improving the efficiency (EEF) of semiconductor solar panels used as electric generators, which can be applied in agrivoltaics projects. Agrivoltaics is a system that simultaneously combines agriculture and solar energy